2018
DOI: 10.1590/0102-311x00052017
|View full text |Cite
|
Sign up to set email alerts
|

Tendências no uso de serviços de saúde médicos e odontológicos e a relação com nível educacional e posse de plano privado de saúde no Brasil, 1998-2013

Abstract: The public-private mix in the Brazilian health system favors double coverage of health services for individuals with private health plans and may aggravate inequities in the use of services. The aim of this study was to describe trends in the use of medical and dental services and associations with schooling and private health coverage. Data were obtained from a national household survey with representative samples in the years 1998, 2003, 2008, and 2013. The study described trends in the use of health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
11
0
14
Order By: Relevance
“…The implementation of these drug distribution programs and policies aimed at providing the population with greater and more equitable access to such products, such as the Generic Medicines Policy and the PFPB 12,13,24 , strongly contribute to explain the study results, in which inequalities in use were found, but not of such magnitude as inequalities found in other areas of health services [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 92%
“…The implementation of these drug distribution programs and policies aimed at providing the population with greater and more equitable access to such products, such as the Generic Medicines Policy and the PFPB 12,13,24 , strongly contribute to explain the study results, in which inequalities in use were found, but not of such magnitude as inequalities found in other areas of health services [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 92%
“…Regarding medical consultations in the last 12 months, according to Viacava and Bellido (2016) [29] in 2013, 71.2% of the Brazilian population reported having had a medical consultation in the last 12 months; and in all regions of the country, except for the North, the increase in the prevalence of medical consultations was significant, between 1998 and 2013. In the general population, the use of health services is higher among adults with private insurance, among women and for people with a higher level of education in all years [30]. However, similar to our study, a study carried out in Serbia [31] found that having multimorbidity reduced the differences in the prevalence of medical visits in these variables, indicating a possible reduction in inequalities in the use of health services in populations with greater health needs, such as the case of people with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding medical consultations in the last 12 months, according to Viacava and Bellido (2016) [29] in 2013, 71.2% of the Brazilian population reported having had a medical consultation in the last 12 months; and in all regions of the country, except for the North, the increase in the prevalence of medical consultations was signi cant, between 1998 and 2013. In the general population, the use of health services is higher among adults with private insurance, among women and for people with a higher level of education in all years [30]. However, similar to our study, a study carried out in Serbia [31] found that having multimorbidity reduced the differences in the prevalence of medical visits in these variables, indicating a possible reduction in inequalities in the use of health services in populations with greater health needs, such as the case of people with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%